Recording and on-line analysis of the earthquakes at the National center of seismological data - І.Ю Гурова; Т.А. Амашукелі; І.А. Калітова (Геофизический журнал, 2021)
The research is dedicated to statistical analysis of such a powerful natural phenomenon as an earthquake and to the problems of monitoring the seismicity in the territory of Ukraine directly. According to evidences of century-old data, annual number and the strengths of earthquakes differ, however its growth is observed definitively. Such a trend needs more attentive attitude to manifestations of seismic activity and its results even within the platform parts of the territory of Ukraine. Examples of registering earthquakes observations of different intensity and remoteness by Ukrainian observation net have been made. Special consideration at the National center of seismological data has been given to seismic vibrations which appear and are fixed in the areas bordering Ukraine and within its territories directly. Essential background for elaboration and successful practical usage of  the medium-term and short-term methods of forecasting the approaching seismic catastrophe or dangerous development of the seismic process which has begun are observation and on-line processing of the earthquakes at the National center of seismological data with successive producing bulletins and catalogues.